Atributos físicos e químicos de um latossolo e produtividade de culturas, em função de manejo de solo e de rotação de culturas - Spera, Silvio Tulio (2010)
The vegetal production is influenced by the soil tillage and by crop rotation. The effect of the interaction of these factors, along the years of cropping, on the grain yields (GY) and on the soil attributes, of the layers explored by the roots of the crops, is not well known. The objective of the work was to evaluate the interaction of these two factors on the GY, crop production, and on the physical and chemical, attributes of two soil layers. The experiment was carried out on a dystrophic Red Latosol (Haplustox), after more than two decades of cropping without liming. It was lead in the Embrapa Trigo, southernmost region of Brazil, and a randomized block design with split plot schedule was used. The following treatments were evaluated: no-till (PD), chisel plow tillage (PM), and conventional plough tillage (PC). These treatments were combined with the crop rotations: wheat/soybean (R1); wheat/soybean-vetch/sorghum (R2) and wheat/soybean-vetch/sorghum-white oat/soybean (R3), to evaluate the effect on the GY and the shoot dry mass (DM) of both the summer and winter crops. The effect of these factors on the soil attributes and macro-morphologic characteristics was also evaluated as a function of the soil layer analyzed (0 to 6.7 and 6.8 to 20 cm). The physical and chemical attributes were not influenced by the interaction of the studied factors and were less affected by the crop rotation. In all treatments, the physical attributes indicated a not compacted superficial layer (0 to 6.7 cm) and a compacted subsurface layer (6.8 to 20 cm). In the not compacted layer, there were not important differences between for treatments physical attributes, but in the PD and PM treatments showed best relevant chemical attributes values (Ca, K, P, Zn and potential CEC) for crop development of evaluated species. The highest values of soil density and the lowest values of macro porosity and the best least limiting water range were found in the compact layer of the PD and PM treatments. In the compact layer of the PD they had increased contents of Mn, and values of CTC. In the soil solution, the PD provided best accumulations of dissolved organic carbon, and lesser percent and activity of Al. The PD mitigated the Al toxicity in the soil solution, in comparison of the other managements. In all treatments and two soil layers, the acidity level of soil and soil solution was restrictive to the development of the evaluated plants. The GY did not vary with the soil tillage, except the sorghum crop; nor with the crop rotation, except the GY of wheat. In evaluated year (2007), the yield of white oats and vetch did not changed with the studied factors, as well as with the interactions between the factors. The crop rotations with four or more species (R2 and R3) increased the production of DM. Non-strong correlations were found between crop yields and chemical and physical attributes of soils, in both layers, even and there are differences in levels of chemical and physical restriction of layers